109k views
0 votes
Expand the expression (x-5)^3

2 Answers

0 votes

Answer:


x^3-15
x^(2)+25x-125

Explanation:

This is a quadratic equation, so we need to open the equation first. There are three (x-5), and then we multiply them together, and then combine like terms to get the answer.

(x-5)(x-5)(x-5)=

[x(x-5)-5(x-5)](x-5)=

(
x^(2)-5x-5x+25)(x-5)=

(
x^(2)-10x+25)(x-5)=

x(
x^(2)-10x+25)-5(
x^(2)-10x+25)


x^3-
10x^2+25x-
5x^2-125=


x^3-15
x^(2)+25x-125

User Tin Megali
by
5.9k points
3 votes
x^3 - 15x^2 + 75x - 125
User Weijian
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.